PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA SANGER WARUNG KOPI ACEH KOTA MALANG - Retno Ayu Dewi Novitawati; Ari Mahfud; Totok Sasongko (Unitri Press, 2019)
This study aims to know and analyze about the influence of quality of product and price to customer loyalty in Sanger Warung Kopi Aceh Malang. This research is quantitative descriptive with all consumers as population, using purposive sampling. The samples obtained amounted to 100 with characteristic of loyal customers with indicators had at least two times made a purchased and recommend a product or service to others. The results showed that simultaneously both of quality and price has influence to loyalty with value of 3.93 and significance of 0,000 005, but separately the quality has influence, while price has no influence to consumers loyality.